Profit maximization model for cloud provider based on Windows Azure platform - Chaisiri, Sivadon (2012)
This paper studies a cloud computing market where a cloud provider rents a set of computing resources from Windows Azure operated by Microsoft. The cloud provider can integrate value-added services to the resources. Then, the services can be sold to customers, and the cloud provider can earn a profit. Moreover, the cloud provider could save much cost and increase higher profit with the 6-month subscription plan offered by Windows Azure. However, the maximization of profit is not trivial to be achieved since the amount of the customers' demand cannot be perfectly known in advance. Consequently, the subscription plan could not be optimally purchased. To deal with such a maximization problem, the paper proposes a stochastic programming model with two-stage recourse. The numerical studies show that the model can maximize the profit under the customers' demand uncertainty.